Suppression of insulin-like growth factor signalling pathway and collagen expression in keloid-derived fibroblasts by quercetin: Its therapeutic potential use in the treatment and/or prevention of keloids - Phan, T.T. (2014)
10.1046/j.1365-2133.2003.05174.x